Simple Empirical Relation for an Evacuated-Tube Solar Collector Performance Prediction from Solar Intensity - Nattapat Pongboriboon; Wei Wu; Walairat Chandra-ambhorn; Patthranit Wongpromrat; Eakarach Bumrungthaichaichan (My University, 2023)
In this paper, the effect of solar intensity on the heat pipe tip temperature in a heat pipe type—evacuated-tube solar collector (HP-ETSC) was investigated. A simple relation was proposed, relating the solar intensity to the heat pipe tip temperature generated from the experimental data. This simple empirical relation was applied in a set of heat transfer equations derived to predict the heating medium temperature at the manifold outlet of the evacuated-tube solar collector. The calculated results corresponding to two types of heating medium, i.e., palm oil and water, were compared with experimental results from the literature. The results show that the average error was 6.41% for the case of palm oil and 4.66% for the case of water. Based on the case of water as a heating medium fluid, it was found that the flow rate of the heating medium fluid affected the accuracy of prediction, as the percentage error increased with the heating medium flow rate. The maximum percentage error increased from only 1.83% for a water inlet flowing at a Reynolds number of about 2.4 × 103 to 15.23% for a water flow rate at a Reynolds number of about 2.6 × 104. The correction factor was added into the correlation to predict the heat transfer coefficients of heating medium fluids. With this correction factor, the maximum error could be reduced from 11.78% to 7.29% for the palm oil case and from 15.23% to 5.57% for the water case. The average errors corresponding to palm oil and water cases could be reduced to 0.74% and 1.26%, respectively.
Keywords: Intensity; Solar water heating; Solar Thermal and Photovoltaic Systems